Resilience in aging concepts, research, and outcomes - Resnick, Barbara; Gwyther, Lisa P.; Roberto, Karen A.; SpringerLink (Online service). (New York Springer, 2011)
Resilience in Aging Concepts, Research, and Outcomes Barbara Resnick, Karen A. Roberto, and Lisa P. Gwyther, editors While medical advances are prolonging the lives of countless older adults, longevity can come at a steep price, such as chronic pain, fatigue, depression, or cognitive decline. To meet this widespread challenge, resilience?the ability to meet and recover from setbacks?has emerged as a promising clinical strategy toward successful aging. The only book devoted solely to the importance and development of resilience in elders? quality of life, Resilience in Aging offers evidence-based theory, clinical guidelines, case examples, and real-world interventions so professional readers can make the best use of this powerful tool, whether one?s clients are in the office or in long-term care, in need of physical or psychological support, worried well or seriously ill. The books coverage extends across disciplines and domains, including: Cultural and ethnic perspectives on resilience in aging. ? Resilience on the job for the older worker. ? Resilience and personality disorders. ? Fostering resilience in chronic illness. Using the arts to promote resilience in persons with dementia. ? Policies to support resilience in an aging society. ? A resilience-building crisis response team. This wide-ranging lifespan approach gives Resilience in Aging particular relevance to the gamut of practitioners in elder care, including health psychologists, neuropsychologists, clinical psychologists, psychiatrists, social workers, geriatricians, family physicians, nurses, and occupational and physical therapists.
Resilience: definitions, ambiguities, and applications -- Successful aging and resilience: applications for public health and health care -- Resilience and personality disorders in older age -- What do we know about resilience in older adults?: an exploration of some facts, factors, and facets -- Psychological resilience -- Physiological resilience -- Using the arts to promote resiliency among persons with dementia and their caregivers -- Promoting worker resilience over the lifecourse -- Resilience in aging: cultural and ethnic perspectives -- Civic engagement: policies and programs to support a resilient aging society -- Strengthened by the spirit: religion, spirituality, and resilience through adulthood and aging -- Resilience in chronic illness -- The relationship between resilience and motivation -- The association between resilience and survival among Chinese elderly -- Fostering resilience in dementia through narratives: contributions of multimedia technologies -- Building resilience in mild cognitive impairment and early-stage dementia: innovative approaches to intervention and outcome evaluation -- African-American caregivers finding resilience through faith -- The age-friendly New York City project: an environmental intervention to increase aging resilience -- Promoting resilience in small-scale, homelike residential care settings for older people with dementia: experiences from the Netherlands and the United States -- A geriatric mobile crisis response team: a resilience-promoting program to meet the mental health needs of community-residing older people -- Optimizing resilience in the 21st century -- Resilience in the workplace: job conditions that buffer negative attitudes toward older workers.
Electronic reproduction.
Keywords: Gerontology; Older people -- Psychology; Resilience (Personality trait); Electronic books